Exploration of inter-professional learning in experiential Learning for student pharmacists in Scotland: A qualitative study. (26th March 2021) - Jebara, T; Power, A; Boyter, A; Jacob, S A; Portlock, J; Cunningham, S
Abstract: Introduction: Additional Cost of Teaching for Pharmacy (ACTp) funding from Scottish Government supports the development of experiential learning (EL) placements for student pharmacists [1]. Interprofessional learning (IPL) has been built into initial education for many healthcare professionals [2]. In 2019, a National Pharmacy EL Stakeholder event recommended exploring the further development of IPL within EL for the MPharm. Aim: To scope existing IPL in EL and explore the feasibility for further development within the MPharm in Scotland Methods: Online qualitative interviews were conducted with key stakeholders from Schools of Pharmacy, NHS Education for Scotland, EL sites, and Scottish health boards. All were involved in the development/delivery of these activities. The interview schedule was developed by the research team, reviewed for face and content validity, piloted prior to use, and modified based on early interviews. All interviews were audio-recorded, transcribed, and independently thematically analysed by two researchers. Interviews continued until data saturation and good representation from all settings were achieved. All ethical approvals were sought prior to the interviews. Results: Twenty interviews were conducted with three key themes emerging; (1)current IPL within EL activities, (2)future developments, and (3)perceptions of enablers and barriers to developing/delivering IPL within EL. There were limited examples of existing IPL within EL activities including: a pilot pharmacy longitudinal clerkship and hospital-based pharmacy/medical student IPL week. Some stakeholders indicated that current IPL involves mainly campus-based activities but other EL based initiatives were planned but not yet implemented. Respondents indicated that future developments should be carefully planned in collaboration with other stakeholders and tailored to students' stage of study to ensure their success. There was significant support for incorporating IPL within EL initiatives as part of the MPharm course to complement traditional ways of teaching. "I think if we don't do it, we're missing a big trick… Doing something in a classroom or doing something within a small tutorial is a very false way of learning, whereas in practice, where they're going to end up working together, it seems ideal." Many enablers were highlighted mainly relating to the expected benefits of such activities on students, facilitators, patients, and the healthcare system. Logistics and planning difficulties were perceived to be barriers to implementation of IPL within EL. "We've tried to do it, it was with the medical school and they were receptive to it, but the logistics just didn't work out… when you've got two very different timetables to try and bring together, it is very, very difficult to do." Conclusion: Pharmacy stakeholders highlighted that the majority of IPL currently undertaken in Scotland is not based in EL settings but they supported developing it. Enablers and barriers articulated highlight the need for careful planning of these activities. A strength of this study is it involved a broad range of key stakeholders from across Scotland ensuring representativeness of views and ideas. A limitation may be that, given the Scottish focus, findings may lack direct transferability to other countries. Future research should focus on designing a framework for developing and implementing IPL within EL in Scotland. References: 1. NHS Education for Scotland, 2020. Experiential learning for student pharmacists in Scotland. [online]. Edinburgh: NHS Education for Scotland. Available from: https://www.nes.scot.nhs.uk/our-work/experiential-learning-for-student-pharmacists-in-scotland/ [Accessed 07/10/2020]. 2. Barr H. Interprofessional Education-The Genesis of Global Movement. 2015. https://www.caipe.org/resources/publications/barr-h-2015-interprofessional-education-genesis-global-movement . [Accessed 4 Aug 2020]